Comparative study between pre- and post- operative clinical and electrophysiological parameters in determining the recovery of carpal tunnel syndrome - Sahoo, Abhinash; Bal, Prasanta K.; Singh, Pruthwiraj; Behera, Syama S.; Sarangi, Ashok K.; Nayak, Alok R.; Sarangi, Anshuman (International Journal of Research in Medical Sciences, 2022)
Background: Carpal tunnel syndrome (CTS) is a neuropathy caused by entrapment of the median nerve at the wrist. CTS is the most well-known and frequent form of median nerve entrapment and accounts for 90% of all entrapment neuropathies. CTS, in the form of median nerve entrapment, remains a perplexing and debilitating disorder. We report a comparative study between the Boston questionnaire (BQ) and median nerve conduction study parameters in patients with CTS treated by division of the flexor retinaculum through a short incision at the palm. Methods: The prospective cross-sectional, hospital-based study was conducted in department of burns, plastic and reconstructive surgery at SCB Medical College, Cuttack. Results: The average age was 44.49 years (SD=10.51; range=24-70), and the average symptom duration was 19.9 months (range=6-36). There are 36 hands in the severe group, 22 with the moderate group, and 12 with the mild category. The mean symptom severity scale score for severe group A was 40.92 (SD=5.84) and for moderate group B was 31.67 (SD=5.72), and for the mild group, C was 26.0 and SD=3.82). We found significant correlation between symptomatic recovery and Boston severity scales. Conclusions: Clinical correlation of pre- and post-op symptoms is the only full proof way to predict recovery after surgery in CTS‑affected, patients.